Feasibility of an endotracheal tube‐mounted camera for percutaneous dilatational tracheostomy. Issue 6 (11th May 2017) - Grensemann, J.; Eichler, L.; Hopf, S.; Jarczak, D.; Simon, M.; Kluge, S.
Abstract : Background: Percutaneous dilatational tracheostomy (PDT) in critically ill patients is often led by optical guidance with a bronchoscope. This is not without its disadvantages. Therefore, we aimed to study the feasibility of a recently introduced endotracheal tube‐mounted camera (VivaSight™‐SL, ET View, Misgav, Israel) in the guidance of PDT. Methods: We studied 10 critically ill patients who received PDT with a VivaSight‐SL tube that was inserted prior to tracheostomy for optical guidance. Visualization of the tracheal structures (i.e., identification and monitoring of the thyroid, cricoid, and tracheal cartilage and the posterior wall) and the quality of ventilation (before puncture and during the tracheostomy) were rated on four‐point Likert scales. Respiratory variables were recorded, and blood gases were sampled before the interventions, before the puncture and before the insertion of the tracheal cannula. Results: Visualization of the tracheal landmarks was rated as 'very good' or 'good' in all but one case. Monitoring during the puncture and dilatation was also rated as 'very good' or 'good' in all but one. In the cases that were rated 'difficult', the visualization and monitoring of the posterior wall of the trachea were the main concerns. No changes in the respiratory variables or blood gases occurred between the puncture and the insertion of the tracheal cannula. Conclusion: Percutaneous dilatational tracheostomy with optical guidance from a tube‐mounted camera is feasible. Further studies comparing the camera tube with bronchoscopy as the standard approach should be performed.